Komunitas Collembola pada Hutan Konservasi dan Perkebunan Sawit di Kawasan PT. Tidar Kerinci Agung (TKA), Sumatera Barat - Rina Oktavianti; Jabang Nurdin; Henny Herwina (Jurnal Biologi Universitas Andalas, 2017)
The research about composition and structure of Collembola community was conducted at TKA company area, west Sumatra. Collembola were collected at oil palm plantation, conservasion forest and forest edge sites (between conservation forest and plantation area) by survey method with systematic random sampling for collembolla in litter and soil. A total of four Collembola species that belonging to 2 orders, 3 families, 4 genera and 57 individuals was collected. The density of Collembola in litter at conservation forest site was higher than density of Collembola at oil palm plantation site meanwhile the density of Collembola in soil at conservation forest site was higher than density of Collembola in the soil at palm plantation site. Relative density of Isotomiella sp. in litter at oil palm plantation site (100%) was higher than relative density of Folsomides sp. at conservation forest site (5,5%) as well as in the soil. The highest diversity index of Collembola was found in litter of conservation forest (1,18). The highest similarity index was found between conservation forest and forest edge (85,71%) meanwhile the lowest similarity index was found between conservation forest and oil palm plantation (40%).